A high resolution DMA covering the 1–67 nm size range. Issue 1 (2nd January 2020) - Perez-Lorenzo, Luis Javier; Khanna, Vaibhav; Meena, Tarun; Schmitt, Jerome J.; de la Mora, Juan Fernandez
Abstract: A differential mobility analyzer for high-mobility resolution ( 1/FWHM ∼30) classification of 1–67 nm particles is designed to analyze viral particles. Inner and outer electrode radii of 1.01 and 2 cm (at the outlet slit) and a 11.6 cm long column achieve this range at a sheath gas flow ( Q ) and aerosol flow ( q ) of 30 and 1 L/min. Turbulent transition potentially resulting from this substantial length combined with high sheath gas flow rates ( Q ∼1000 Lit/min) required to classify 1 nm particles is avoided by stabilizing the flow via a continuous acceleration with a conical inner electrode (1° half-angle). High axisymmetry of the aerosol flow as it joins the sheath gas is achieved by injecting it through a circularize r ring with 24 symmetrically spaced orifices. The sheath flow is laminarized with two pre-laminarization schemes, three laminarization screens, and an inlet trumpet with an area ∼3 times the analyzer channel throat area. The instrument is tested with singly charged monomobile cluster ions produced by a bipolar electrospray source. A resolving power of 29 is measured at the highest flow rate reached, with a trend towards even higher resolution if either Q or the monomobile particle size could be increased. This performance indicates that the electrode concentricity is excellent and the flow highly stable. Tests carried out at limited resolution (set below 16 by a protein test aerosol) with the modest Q/q ∼30 values required to classify 70 nm particles indicate that the DMA response is close to ideal at Q = 151, 110, and 47 Lit/min. Copyright © 2019 American Association for Aerosol Research